Exploration of the Majapahit Cultural Tourism Village Governance - Harjo Lukito; Swasti Ayu Natalia; Jason Eka Candra Lukito (International Journal of Religious and Cultural Studies, 2023)
This research explores the governance of the Kampung Majapahit Cultural Tourism Village with a focus on collaborative work. Primary data was obtained through interviews and observations for two months using the qualitative research. Important findings include suboptimal implementation of the educational tourism concept, important cross-sector collaboration and community participation, as well as incentives for stakeholders. Scheduled evaluations with cycles of deepening mutual trust, commitment and understanding are an integral part of the management of the Kampung Majapahit Cultural Tourism Village. This research provides theoretical and practical contributions in understanding community-based tourism governance in Indonesia.